Orientación vocacional deportiva: una revisión de la literatura (2022)
Objective: to present the knowledge available in the literature on sports vocational guidance and to observe its application as a tool to promote health and quality of life. Methodology: the research is a qualitative and quantitative study, structured in an integrative review, conducted from September to October 2020 with the use of materials published between 2012 and 2020 in Lilacs, SciELO and PubMed databases. Keywords and inter-terms were considered from prospecting in descriptors in Health Sciences (DeCS/MeSH), with the search being structured in the Pico strategy. Results: 490 results were found among abstracts, articles and theses. After a preliminary analysis, 28 articles were selected for a comprehensive analysis, of which 23 were included in the study. It was found that the sports orientation process can be carried out with the support of specific tools, such as VocSports®. Conclusions: the study confirms the need for a correct sports vocation guidance to achieve greater adherence and, consequently, lasting beneficial effects on the health and quality of life of the populations, and proposes a public policy option to achieve this objective.